Carrier initial phases estimation for single-channel adjacent-frequency mixture of digitally modulated signals - Yong YANG; Yi-ming GUO; Hai-xin WANG; Hua PENG; Dong-ling ZHANG (Tongxin xuebao)
For single-channel mixture of adjacent-frequency digitally modulated signals which have the fixed frame length and sync codes in non-cooperative satellite communications,a carrier initial phases estimation algorithm which can be applied to both low-order and high-order digitally modulated mixtures was provided according to the differences of parameters in the source signals.The sync data eliminated the frequency offset was added in the interval of frame length firstly,then timing synchronization was accomplished for the added result in terms of power maximization rule,thus the initial phases information was derived.Moreover,the modified Cramer-Rao bound (MCRB) of carrier initial phases for single-channel mixture of adjacent-frequency digitally modulated signals was derived for comparison.Simulation results show that,difference between estimation performance of the proposed algorithm and MCRB becomes smaller with the increase in the number of added frames.